2007
DOI: 10.1128/aac.01160-06
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Effects of Caspofungin on the Metabolic Activity of Aspergillus Species

Abstract: The minimum effective concentration (MEC) used to assess the in vitro antifungal activity of caspofungin against Aspergillus spp. is a qualitative endpoint requiring microscopic examination of hyphae. We therefore developed a tool for the quantitative assessment of caspofungin activity against Aspergillus spp. at clinically applicable concentrations. Susceptibility to caspofungin (0.008 to 8 g/ml) was studied for 9 A. fumigatus, 8 A. flavus, and 12 A. terreus isolates based on the Clinical and Laboratory Stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 26 publications
4
44
0
Order By: Relevance
“…This hypothesis is consistent with the observation that deletion of ERG genes increased caspofungin susceptibility (18). The antagonistic effects of the double combinations voriconazole-caspofungin and amphotericin B-caspofungin at high caspofungin concentrations may be associated with the paradoxical increase of fungal growth observed recently with an in vitro colorimetric assay of fungal metabolic activity at high caspofungin concentrations similar to those found in the present study (1). Thus, the antagonistic interactions within the triple combination observed at high amphotericin B and voriconazole concentrations are due to the antagonism between amphotericin B and voriconazole, while the synergistic interactions within the triple combination observed at lower amphotericin B and voriconazole concentrations are due to the synergistic interactions of voriconazolecaspofungin and amphotericin B-caspofungin combinations.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This hypothesis is consistent with the observation that deletion of ERG genes increased caspofungin susceptibility (18). The antagonistic effects of the double combinations voriconazole-caspofungin and amphotericin B-caspofungin at high caspofungin concentrations may be associated with the paradoxical increase of fungal growth observed recently with an in vitro colorimetric assay of fungal metabolic activity at high caspofungin concentrations similar to those found in the present study (1). Thus, the antagonistic interactions within the triple combination observed at high amphotericin B and voriconazole concentrations are due to the antagonism between amphotericin B and voriconazole, while the synergistic interactions within the triple combination observed at lower amphotericin B and voriconazole concentrations are due to the synergistic interactions of voriconazolecaspofungin and amphotericin B-caspofungin combinations.…”
Section: Discussionsupporting
confidence: 81%
“…However, combinations with higher doses of caspofungin (2.5 mg/kg) may result in higher CFU per gram than combinations with lower caspofungin doses (1 mg/kg) (14), consistent with the concentration-dependent interactions that we found in the present study. This apparent increase in fungal burden in vivo may be caused by dosage-dependent hyphal fragmentation (1,32,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a different colorimetric marker (XTT), Antachopoulos et al also reported a proportionate species-dependent reduction in metabolic activity at the MEC for all Aspergillus isolates tested, which was more pronounced for A. flavus (median metabolic activity 25% of control) compared to A. fumigatus and A. terreus (median metabolisms of 42 and 53%, respectively) (17). Thus, the current alamarBlue concentration may be sufficient for the slower-growing A. fumigatus and A. terreus but not for the fast-growing A. flavus.…”
Section: Discussionmentioning
confidence: 99%
“…For most experiments, strains were grown on YEPD agar (1% yeast extract, 2% peptone, 2% dextrose, 1.5% agar) at 37°C. Some experiments required the use of Aspergillus minimal medium containing trace elements (Na 2 4 ), 1% glucose, and NaNO 3 adjusted to pH 6.5. Media used in specific experiments included Aspergillus minimal medium containing 0.5% glucose (Aspergillus minimal glucose medium), Aspergillus minimal glucose medium supplemented with 0.5% trehalose, and Aspergillus minimal glucose medium supplemented with 1 M sorbitol.…”
Section: Methodsmentioning
confidence: 99%